Pengaruh tax planning, tax avoidance, dan manajemen laba terhadap nilai perusahaan - Reeza Aldila Rajab; Alfiyyah Nikmah Taqiyyah; Fitriyani Fitriyani; Khairina Amalia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This research aims to determine the effect of independent tax planning, tax avoidance, and earnings management on firm value. The data used in this research is obtained from the annual report of financial statements on non consolidation manufacturing companies listed in the Indonesian Stock Exchange period 2015- 2017. The sample selection method used is the purposive sampling method. Analytical techniques used in this research using multiple linear regression which include normality test, test classic assumptions, and hypothesis testing. The total sample in this research is 10 companies. Data processing in this research using Eviews version 9.0 application. The result shows that tax planning, tax avoidance, and earnings management simultaneously have an effect on firm value. In addition, this study proves that earnings management has a negative effect on firm value, while tax planning and tax avoidance have no effect on firm value.